2011
DOI: 10.1097/bsd.0b013e3181cc90f2
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Versus Nonrigid Occipitocervical Fusion

Abstract: In addition to the many advantages of a rigid occipitocervical construct, the clinical complication rates are statistically significantly lower versus a nonrigidly fixed construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Despite the perceived difficulties of atlanto-axial fusion difficulties, several retrospective reviews have suggested increased complications such as non-union, neuralgia, sepsis, and return to OR following occipitocervical compared to altanto-axial fusion with no difference in functional outcomes as measured by Neck Disability Index [5][6][7] . However, occipitocervical fusion has yet to be compared to atlanto-axial fusion in a matched analysis [8][9][10] . The goal of this investigation was to compare complications, revision rate, and prolonged opioid use between occipitocervical fusion and atlanto-axial fusion patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the perceived difficulties of atlanto-axial fusion difficulties, several retrospective reviews have suggested increased complications such as non-union, neuralgia, sepsis, and return to OR following occipitocervical compared to altanto-axial fusion with no difference in functional outcomes as measured by Neck Disability Index [5][6][7] . However, occipitocervical fusion has yet to be compared to atlanto-axial fusion in a matched analysis [8][9][10] . The goal of this investigation was to compare complications, revision rate, and prolonged opioid use between occipitocervical fusion and atlanto-axial fusion patients.…”
Section: Introductionmentioning
confidence: 99%